Clinical study on the effects of diacerein and diacerein combined with chondroitin sulfate on canine hip osteoarthritis - Korakot Nganvongpanit (2018)
This study aimed to evaluate the effects of diacerein (DAR) and DAR combined with chondroitin sulfate (CS) for treatment of canine hip osteoarthritis (OA) in a 6-month clinical trial. Client-owned dogs included in the study consisted of 27 males and 25 females, aged 59.43±17.05 months old and weighing 17.63±5.19 kg. The dogs were randomly divided into five groups: DAR50 (administration of DAR 50 mg daily); DAR100 (DAR 100 mg daily); DAR50/CS (DAR 50 mg + CS 525 mg daily); DAR100/CS (DAR 100 mg + CS 525 mg daily); and CS (CS 525 mg daily). Dogs were re-examined monthly for 6 months after initiation of treatment. The assessment protocol included clinical scores and radiographic findings. Blood samples were collected three times (pre-treatment, and after 3 and 6 months) for evaluation of the serum biomarker, CS-WF6. Dogs treated with DAR showed statistically significant improvements (P < 0.05) in lameness, joint mobility, pain on palpation, weight-bearing, and overall clinical score at 3, 6, 5, 4, and 4 months, respectively, after the start of treatment. Side effects, including diarrhea and dark-colored urine, were found in all groups receiving DAR. After the 3 rd month, the level of serum CS-WF6 in the CS group was significantly elevated (P < 0.05), while the other four groups showed a significant decrease (P < 0.05). The results showed that DAR 50 or 100 mg had a similarly positive therapeutic effect on dogs with osteoarthritis. The use of DAR alone or in combination with CS resulted in decreased degradation of OA cartilage.